Pengembangan Sistem Informasi Deteksi Dini Penyakit Tidak Menular (PTM) dengan Pendekatan Rapid Application Development (RAD) - Tubagus Agung Nugroho; Adam Hendra Brata; Edy Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The dominance of non-communicable diseases (NCDs) has increased global attention to NCDs. Puskesmas is one of the frontlines in carrying out community service efforts including controlling NCDs. The use of information technology systems is needed in various fields, one of which is in the health sector. By using this NCDs early detection information system, officers will be able to facilitate data collection and search, reduce the occurrence of double data in the data, find out more quickly and precisely how many patients are affected by NCDs, and rapid distribution of NCDs data to the ministry of health. So that the impact on the puskesmas will help achieve the required program targets. The non-communicable disease (NCDs) early detection information system was built using the RAD (Rapid Application Development) method. The results of the examination will immediately determine how many patients are affected by NCDs. this system will be implemented using the visual studio code framework with javascript, html, and using phpmyadmin as a database to store data. This system gets 21 functional and 1 non-functional, and gets 2 actors, namely admin and health workers. This system test uses 3 ways, namely unit testing with the whitebox method, validation testing with the blackbox method, and compatibility testing. Whitebox testing uses 3 algorithm data and manages to get a 100% valid value with the system algorithm flow as expected. Blackbox testing managed to get 100% valid results on all tested functionality because it was in accordance with the expected results. Compatibility testing managed to get 100% valid results on the tested non-functionality because the system can be run on several web browsers.